2010
DOI: 10.1016/j.febslet.2010.03.040
|View full text |Cite
|
Sign up to set email alerts
|

ROS leads to MnSOD upregulation through ERK2 translocation and p53 activation in selenite‐induced apoptosis of NB4 cells

Abstract: Edited by Vladimir Skulachev Keywords:Manganese superoxide dismutase Reactive oxygen species Extracellular regulated kinase Nuclear translocation p53 a b s t r a c t Following our previous finding that sodium selenite induces apoptosis in human leukemia NB4 cells, we now show that the expression of the critical antioxidant enzyme manganese superoxide dismutase (MnSOD) is remarkably elevated during this process. We further reveal that reactive oxygen species (ROS), especially superoxide radicals, play a crucial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 46 publications
(54 reference statements)
7
53
1
Order By: Relevance
“…Accumulating evidences confirmed the application of selenite in studies of cell proliferation and cancer (3,4). Previous results suggested supranutritional doses of selenite promoted cell death through mitochondria-or ER stress-mediated apoptotic pathway in human leukemia cell lines (5,6). Furthermore, autophagy has recently been considered as an alternative mechanism of cell death induced by selenite, which caused concurrence of autophagy and apoptosis in leukemia cells (7,8).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Accumulating evidences confirmed the application of selenite in studies of cell proliferation and cancer (3,4). Previous results suggested supranutritional doses of selenite promoted cell death through mitochondria-or ER stress-mediated apoptotic pathway in human leukemia cell lines (5,6). Furthermore, autophagy has recently been considered as an alternative mechanism of cell death induced by selenite, which caused concurrence of autophagy and apoptosis in leukemia cells (7,8).…”
Section: Introductionmentioning
confidence: 78%
“…Previous studies indicated that the antitumor activity of selenium compounds was often attributed to drug-induced apoptosis (5,6,20). Here we addressed that autophagy acted as another essential mechanism for the application of selenite in cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…We have also shown that the level of ROS is maintained to its sub-lethal concentration by upregulation of SOD-1. This can be correlated with a feedback response related to increasing in ROS production by cristacarpin, which eventually maintains the sub-lethal concentration of ROS essential for senescence (Li et al 2010). The detailed mechanism is under investigation of our laboratory.…”
Section: Discussionmentioning
confidence: 94%
“…Detection of Reactive Oxygen Species (ROS) ROS generation by VSMCs was measured with ROS assay kit (Beyotime, China) according to the manufacturer's instruction. 19) In brief, VSMCs were cultured in 6-well plates and synchronized by DMEM without serum overnight. VSMCs were treated with 100 µM naringenin for 30 min and then exposed to 1 µM angiotensin II for 1 h. Cells were then incubated with 10 µM 2,′7′-dichlorodihydrofluorescein diacetate (DCFH-DA) for 30 min in dark at room temperature.…”
Section: Methodsmentioning
confidence: 99%